PENGEMBANGAN PELAYANAN TERHADAP SIMPAN PINJAM DI BMT-UGT NUSANTARA GONDANGLEGI - Fanreza, Aditia; Ibrahim, Wahyu Malik; Anas, M. Yusuf Azwar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research discusses the development of savings and loan services based on sharia principles implemented by BMT UGT Nusantara Gondanglegi. The main focus of the research is how this institution improves the quality of service to answer member needs and current challenges. With a qualitative descriptive approach, data was obtained through field observations, interviews, and literature studies during Field Work Practice (PKL) activities. The findings show that BMT has implemented various innovative strategies, such as using simple technological devices to speed up field transactions and increasing employee competency through continuous training. Even so, obstacles are still found such as limitations in digitalization and adaptation to new technological systems. This study suggests the need for more massive integration of information technology and consistent human resource development to answer the demands of sharia microfinance services in the modern era.